Menggunakan Facebook Sebagai Media Promosi Pada CV. Putra Sarya Pratama - Ardijan Handijono; Rudy Irawan Gunarto; Samsul Marpitasa; Aditya Riky Nugroho; Reno Virlandana (Universitas Pamulang, 2021)
Using Facebook As A Promotional Media On CV Putra Sarya Pratama - Small and Medium Enterprises (SMEs) play an important role in the economy in Indonesia. CV Putra Sarya Pratama, having his address in Depok, started his business on January 1, 2021, ago. This business focuses on providing Generic Medicines, Vitamins, Supplements and Baby equipment for the surrounding community. From observing how the daily business processes are, and conducting interviews with the owner, how to manage business finances, how to market it, and what are the main obstacles to the business. We found one of them is the high cost of promotion. The purpose of this PKM is to increase sales with social media-based promotions. There are several solutions that we offer. The approach we use is through presentations, question and answers and discussion, as well as mentoring that begins with brainstorming to open a mindset about the importance of treating business more professionally according to the times. After this PKM activity, it is hoped that partners can use Social Media as a cheap and effective promotional tool, to introduce their products and expand their sales reach so as to increase business and business profits. From this PKM activity, it can be seen that technology, especially Social Media, has significantly contributed to determining the success or failure of a business in the current information age.